2021
DOI: 10.2147/vhrm.s298436
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis in Young Patients with Acute Coronary Syndrome Treated with Percutaneous Coronary Intervention

Abstract: Background: Acute coronary syndrome (ACS) at a young age is uncommon. Limited data regarding the long-term follow-up and prognosis in this population are available. Our objectives were to evaluate the long-term clinical outcomes of patients presenting with ACS at a young age and to assess factors that predict long-term prognosis. Methods: A retrospective analysis of consecutive young patients (male below 40 and female below 50 years old) that were admitted with ACS and underwent percutaneous coronary intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…There are identical results for the high 15-year mortality in patients with early myocardial infarction in a long-term survival study [31]. Overall, 65% of patients had at least one serious cardiovascular event and/or death in the study Yagel and colleagues, examining cardiovascular outcomes in patients with early acute coronary syndrome [32]. More, than half (52.9%) of patients with early CHD had at least one cardiovascular event during 10 years of follow-up in another study of long-term prognosis [33].…”
Section: Discussionmentioning
confidence: 73%
“…There are identical results for the high 15-year mortality in patients with early myocardial infarction in a long-term survival study [31]. Overall, 65% of patients had at least one serious cardiovascular event and/or death in the study Yagel and colleagues, examining cardiovascular outcomes in patients with early acute coronary syndrome [32]. More, than half (52.9%) of patients with early CHD had at least one cardiovascular event during 10 years of follow-up in another study of long-term prognosis [33].…”
Section: Discussionmentioning
confidence: 73%
“…In addition, there was no significant difference between the ACS types regarding hypertension, diabetes mellitus, and hyperlipidemia. In comparison, the prevalence of hypertension, diabetes mellitus, and hyperlipidemia in young patients with ACS were 20%, 15%, and 57%, respectively as revealed in another study that was done by Yagel et al [15]. In concordance, Arantes et al [13] concluded that dyslipidemia was a significant risk factor for ACS in the young population.…”
Section: Discussionmentioning
confidence: 83%
“…Thomas et al [ 14 ] showed that younger participants had a reduced prevalence of hypertension (14.2% vs. 28.3%; p < 0.001) in comparison to the older ones, in a cohort ST-segment elevation myocardial infarction (STEMI) research study on 2420 patients (591 of whom were under 45 years old). In addition, Yagel and co-workers observed that the prevalence of hypertension in the initial ACS incident was low, only in 20% of males below 40 and females below 50 years old, but the most important risk factor for recurrent cardiovascular events was hypertension ( p = 0.0048) [ 15 ]. In addition, a retrospective study revealed that the prevalence of untreated hypertension was higher in patients <55 years (40.4 percent) than in those between 55 and <70 years (27.2%) ( p = 0.007) [ 16 ].…”
Section: Resultsmentioning
confidence: 99%